Infrared thermography for evaluating asymmetry on football players in the pre-season - Robert, Ellian (2024)
Introduction: The participation of science in the development of high-performance sports is increasingly expressive. Therefore, infrared thermography has been used in order to verify its ability to determine the magnitude of the internal load of official matches to which the athletes are being submitted. Objective: To evaluate football players in the pre-season using infrared thermography. Materials and Methods: The sample consisted of 15 soccer players (age: 19.0 ±0.9 years; body mass: 70.3 ±8.0 kg; height: 176.2 ±0.1 cm; fat percentage: 5.7 ±1.8%F). The evaluation of body composition was carried out and subsequently the infrared thermography. Results: The highest percentage of thigh pixels are related to the hot temperature zone in both the anterior (49%, 35% to 54%) and posterior axis (46%, 42% to 53%). The highest percentage of leg pixels are related to the cold temperature zone in both the anterior (39%, 33% to 46%) and posterior axis (45%, 29% to 55%).  When checking the asymmetry between lower limbs in the anterior and posterior axis, no significant differences were found between the thighs (right and left) and legs (right and left) in the different temperature zones. Conclusion: The present study contributed to a better understanding of the physical state of athletes in the pre-season period. The increases in percentages of pixels in the hot zone temperature indicate the physiological stress related to the inflammatory state of the athletes, being important for the technical staff and the medical department in an attempt to adjust and manage the training and recovery load within game periods.